Pentingnya Pendidikan Ekonomi dalam Mempersiapkan Generasi Muda Menghadapi Tantangan Ekonomi Global - Rambe, Khoirunnisa Fadilla (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2024)
Globalization and technological developments have brought major changes to the economic world. The young generation as the nation's successor needs to be prepared to face these various global challenges. Economic education is an important key in equipping them with the knowledge and skills needed. This article aims to examine the importance of economic education in preparing the younger generation to face global economic challenges. This research uses qualitative methods with literature studies. Data was collected from various trusted sources such as scientific journals, books and online articles. Economic education has an important role in preparing the younger generation to face global economic challenges. This education can equip them with knowledge of economic concepts, the global economic system, and the skills needed to work in the era of globalization. Economic education must be a top priority in the education of the younger generation. Governments, schools and parents need to work together to improve the quality of economic education and ensure that all young people have equal access to this education.